Tillfälleslitterära transformationer - Öhrberg, Ann (Tidskrift för litteraturvetenskap, 2012)
Transformations of Epideictic in Eighteenth-Century Sweden In early modern Sweden, epideictic literature was an important part of the country’s social and cultural life. Occasional texts were written and read in connection with weddings, funerals, coronations etc., mainly by members of the higher and middle social strata. The close connection to socio-cultural circumstances makes this kind of literature an indicator of different historical changes regarding, for example, gender, rhetorical and literary ideals, and the media. In this essay, some of these changes, referred to as transformations of epideictic, are explored with regard to mid-18th century Sweden, when the slowly emerging public sphere brought about changes in public communication. Theories of epideictic in classical rhetoric (Aristotle, Quintilian, Cicero) and Swedish contemporary school rhetoric provide an introductory context. Next, two examples are discussed: first an essay with a subsidiary funeral poem written by Hedvig Charlotta Nordenflycht in which she introduces a new programme for the composition of panegyrics. Her programme indicates a new role for authors and suggests new publication strategies, as well as expressing enlightenment ideals and radical ideas of gender. Secondly, occasional poems written by the Moravian author Magnus Brynolph Malmstedt are analyzed. To propagate Moravian ideas was forbidden in Sweden at the time, but Malmstedt managed nevertheless to introduce his religious programme in public by using the seemingly harmless form of occasional poetry. The text discussed in the essay transcends the normative boundaries both from a political and rhetorical perspective while also mediating new ideas of communication, identity and civic authority.